Extracellular vesicles from hiPSC-derived NSCs protect human neurons against Aβ-42 oligomers induced neurodegeneration, mitochondrial dysfunction and tau phosphorylation - Shama Rao; Leelavathi N. Madhu; Roshni Sara Babu; Goutham Shankar; Sanya Kotian; Advaidhaa Nagarajan; Raghavendra Upadhya; Esha Narvekar; James J. Cai; Ashok K. Shetty (Stem Cell Research & Therapy)
Abstract Background Alzheimer’s disease (AD) is characterized by the accumulation of amyloid beta-42 (Aβ-42) in the brain, causing various adverse effects. Thus, therapies that reduce Aβ-42 toxicity in AD are of great interest. One promising approach is to use extracellular vesicles from human induced pluripotent stem cell-derived neural stem cells (hiPSC-NSC-EVs) because they carry multiple therapeutic miRNAs and proteins capable of protecting neurons against Aβ-42-induced toxicity. Therefore, this in vitro study investigated the proficiency of hiPSC-NSC-EVs to protect human neurons from Aβ-42 oligomers (Aβ-42o) induced neurodegeneration. Methods We isolated hiPSC-NSC-EVs using chromatographic methods and characterized their size, ultrastructure, expression of EV-specific markers and proficiency in getting incorporated into mature human neurons. Next, mature human neurons differentiated from two different hiPSC lines were exposed to 1 µM Aβ-42o alone or with varying concentrations of hiPSC-NSC-EVs. The protective effects of hiPSC-NSC-EVs against Aβ-42o-induced neurodegeneration, oxidative stress, mitochondrial dysfunction, impaired autophagy, and tau phosphorylation were ascertained using multiple measures and one-way ANOVA with Newman-Keuls multiple comparisons post hoc tests. Results A significant neurodegeneration was observed when human neurons were exposed to Aβ-42o alone. Neurodegeneration was associated with (1) elevated levels of reactive oxygen species (ROS), mitochondrial superoxide, malondialdehyde (MDA) and protein carbonyls (PCs), (2) increased expression of proapoptotic Bax and Bad genes and proteins, and genes encoding mitochondrial complex proteins, (3) diminished mitochondrial membrane potential and mitochondria, (4) reduced expression of the antiapoptotic gene and protein Bcl-2, and autophagy-related proteins, and (5) increased phosphorylation of tau. However, the addition of an optimal dose of hiPSC-NSC-EVs (6 × 109 EVs) to human neuronal cultures exposed to Aβ-42o significantly reduced the extent of neurodegeneration, along with diminished levels of ROS, superoxide, MDA and PCs, normalized expressions of Bax, Bad, and Bcl-2, and autophagy-related proteins, higher mitochondrial membrane potential and mitochondria, enhanced expression of genes linked to mitochondrial complex proteins, and reduced tau phosphorylation. Conclusions An optimal dose of hiPSC-NSC-EVs could significantly decrease the degeneration of human neurons induced by Aβ-42o. The results support further research into the effectiveness of hiPSC-NSC-EVs in AD, particularly their proficiency in preserving neurons and slowing disease progression.